Relationship of Age, Gender, Duration of Disease and Retinopathy in Type 2 Diabetes Mellitus Patients - Zahrotunnisa Arizky; Kurniasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The incidence of diabetes mellitus is increasing every year. Indonesia is ranked fifth country with the highest number of people with diabetes mellitus in the world. One of the complications that often occurs is diabetic retinopathy. This study aims to analyze the relationship between age, gender, duration of diabetes mellitus type 2 and diabetic retinopathy. This research is an analytical observational with a cross-sectional approach. All variable data in this study was obtained from medical records. A total of 91 samples were selected using consecutive non random sampling techniques. The chi square test showed a relationship between age (p=0,044; p<0,05), gender (p=0,040; p<0,05), duration of DM type 2 (p=0,046; p<0,05) and diabetic retinopathy. Age, gender, and duration of DM type 2 are factors that cannot be modified and affects the occurrence of retinopathy diabetic